2014 Section on Pediatrics Knowledge Translation Lecture: Clinicians and Researchers on the Same Path Toward Facilitating Family Goals for Mobility and Participation. Issue 2 (2015) - Damiano, Diane L.; Leonard, Rebecca
Abstract : Background: The knowledge translation (KT) lecture at the Combined Sections Meeting 2014 was a personal perspective from a researcher who had been a therapist and a longtime clinician, now a PhD candidate. Objective: To better integrate research and clinical care, KT is a seamless rather than separate process. Key Points: Knowledge translation can be enhanced by improved receptivity to evidence, and increasing use of research designs that encourage and even require clinician involvement, from single-subject designs to large-scale pragmatic trials. Clinical practice databases and hiring therapists to provide intervention in research efforts also serve to integrate research and clinical care. Limitations of applying mean group research results to an individual patient were also discussed and suggest an important unanswered topic for future research. Conclusion: We all need to assume responsibility for the researcher-clinician partnership, making our jobs more joyful and fulfilling, and hopefully the biggest beneficiaries will be our current and future patients. Abstract : This lecture, presented at the 2014 Combined Sections Meeting, describes collaboration opportunities a researcher-clinician pair have experienced that promote knowledge translation for the benefit of the children and families we serve.